VALIDITAS ISI ALAT UKUR PENELITIAN KONSEP DAN PANDUAN PENILAIANNYA - Ihsan, Helli (Universitas Pendidikan Indonesia, 2015)
There are many definitions of the validity of the content but Haynes et al . (1995 ) managed to make an excellent definition so that each phrase of the definition is well described by him . From the description that he created , the author tries to apply it in the form of creating content validity assessment table . The assessment guide contains a quantitative assessment of the elements of measuring instruments, the relevance of the statement of the definition of conceptual and critical operations and how well the structure of language and simplicity sentence in a deciphering statement. This can be used as guidelines testing the validity of the content in the manufacture of measuring instruments in Indonesia .Keywords: Instrument, Validity, Evaluation, Research